Analisis Tingkat Kepuasan Pelanggan Terhadap Pelayanan Apotek Kimia Farma Jakarta Menggunakan Model Servqual (Studi Kasus Pada Tiga Apotek) - Mas’ud, Mas’ud (UI Scholars Hub, 2009)
Since policy sector pharmaceutical affairs 1993 by government about deregulations sector community pharmacy, competition business community pharmacy in Jakarta was very strict. For win something this competitions, Kimia Farma community pharmacy as the biggest community pharmacy network in Indonesia have propagan-dized vision be the foremost business networking community pharmacy in Indonesia and mission first-rate services for customers with customer satisfaction. The objec-tive of this research is detect satisfaction level of service quality of Kimia Farma community pharmacy Jakarta, in particular Kimia Farma community pharmacy -1 Kemayoran, Kimia Farma community pharmacy-48 Matraman, Kimia Farma com-munity pharmacy-147 Duren Sawit. Beside This research also objective for knowed vision, mission of Kimia Farma community pharmacy was reached. This research using survey method with quisionaire Single Cross Sectional Study approaches. Research using Servqual (Service Quality) model was discovered by Parasuraman, Zeithaml and Berry use five dimensions of service quality, that was tangible, reli-ability, responsiveness, assurance, and emphaty. Satisfaction level measured with Gap analysis that was difference expectation before customer receiving the service and perception after that; and Cartesian Diagram analysis, that was mapping atribut service quality on Cartesian Diagram. Analysis difference on customer satisfaction within community pharmacy used analysis varian (Anova). Result: dimension that highest satisfaction level was emphaty (gap -0.37 or satisfactions levels 91.88 %); attribute that highest satisfaction level was well designed interior/exterior building (gap -0.14 or satisfaction levels 96.4 %). Mapping attribute on Cartesian Diagram majority on quadrat B, means service quality Kimia Farma community pharmacy was sufficient. Based on hypothesis test, was not difference significant satisfactions level Kimia Farma community pharmacy was research (alpha > 0.05). Conclusions: generally satisfactions level Kimia Farma community pharmacy that researched nearly satisfy, with satisfaction levels within community pharmacy was not significant difference.